NEW APPROACHES TO THE RESTRUCTURING OF THE RAILWAY INDUSTRY OF UKRAINE - Shyrokova, O. M. (Science and Transport Progress, 2008)
In the article the basic results of analysis of railway transport work are presented. The structure, activity of which is not enough effective, is determined. The innovative measure of conducting of restructuring the railway industry of Ukrzaliznytsia is suggested.